A Silver Achaemenid Rhyton from the South Urals: A Complex Archaeometallurgical Study and Modern Restoration - Treister, Mikhail Yu.; Vergazov, Ramil R.; Tulubensky, Mikhail G. (Anabasis. Studia Classica et Orientalia, 2020)
The State Pushkin Museum of Fine Arts in Moscow acquired in 1972 a fragmented silver rhyton with a horse protome, which was found in 1971 in one of the burial mounds of the Novyī Kumak necropolis in the South Urals, dating to the 5th–4th centuries BC. This rhyton was most probably received by the nomadic elite of the Sarmatians as a trophy or gift. The rhyton belongs to the Achaemenid style, with the closest parallels from the Erebuni Treasure in Armenia, dating back to the second half of the 5th–first half of the 4th century BC, probably manufactured in one of the workshops of Eastern Anatolia. Details of the treatment of the vessel, first of all, the horse harness, find close parallels among other Achaemenid rhyta, also from the Treasure of Borovo in Thrace, as well as on the Apadana and Palace H reliefs from Persepolis. The fragments of the rhyton were examined by Igor Chernyshev and Andrey Chugaev at the Institute of Geology of Ore Deposits, Petrography, Mineralogy and Geochemistry, Russian Academy of Scienсes, Moscow, using the method of inductively coupled plasma multicollector mass spectrometry (MC-ICP-MS) with mass spectrometer of the Neptune series (Thermo-Finnigan). The micro-X-ray fluorescence analysis was performed by Grigory Kuznetsov at the Bruker Nano Department Russia and CIS with the M1 MISTRAL spectrometer. The Pb-Pb data suggest that the metal (fineness 990) originates from the deposits of Asia Minor or Iran. The first restoration of the rhyton in 1972 was produced in violation of the general proportions. The inner wire frame has corroded. The new restoration executed in the laboratory of the Pushkin Museum by Mikhail Tulubensky in 2020, using modern materials and techniques (the polymer model and laser welding) made it possible to recreate the original appearance of the rhyton.